Quantification of Metabolic Acidosis at Bedside by S.A.L.T Approach - Harshitha Seshadri; Anitha Nileshwar; Shwethapriya Rao; Nisha Sara M. Jacob (Journal of Emergencies, Trauma and Shock)
Introduction: Traditionally, metabolic acidosis is analyzed using an anion gap (AG). The aim of the study was to compare the utility of quantitative David Story’s simplified Stewart approach against traditional approach to analyze metabolic acidosis. ICU setting. Analytical, cross-sectional observational study. Methods: Blood gas reports of 50 adult critically ill patients with primary metabolic acidosis at admission were analyzed using both approaches. With traditional approach, acidosis was classified simply as high or normal AG acidosis. With S.A.L.T approach, the components of base deficit were further quantified into sodium chloride, albumin, lactate, and other ions effects. A contribution of sodium chloride or albumin effect of > 30% to the base deficit was considered significant. The proportion of patients with such abnormalities was determined. Descriptive statistics was used. Results: The mean ± standard deviation (SD) age of patients was 54.52 ± 19.71 years, 52% were males, and 72% were medical admissions. The median (interquartile range [IQR]) Sequential Organ Failure Assessment score was 10 (5–13). The mean ± SD pH, bicarbonate, base excess, and albumin were 7.198 ± 0.13, 11.73 ± 4.2 mmol/L, −15.13 ± 5.6 mmol/L, and 2.9 ± 0.77 g%, respectively. The median (IQR) of serum lactate was 6.77 (1.53, 16.32) mmol/L. Hyponatremia and hypochloremia were seen in 68% and 46% of patients, respectively. Eighty-eight percent of patients had acidosis due to other ions, 52% due to lactates. Twenty-eight percent had a significant sodium chloride effect and 32% had significant hypoalbuminemia. Conclusion: Quantification of base deficit of metabolic acidosis using S.A.L.T approach showed changes in sodium chloride levels and hypoalbuminemia affecting base deficit in nearly 30% of the patients. Quantification of metabolic acidosis using S.A.L.T approach is likely to help treat metabolic acidosis more appropriately, with clinical implications.